Robust identification by dynamic neural networks using sliding mode learning - Poznyak, Alexander S.; Yu, Wen; Sanchez, Edgar N.; Sira-Ramirez, Hebertt (Zielona Góra: Uniwersytet Zielonogórski)
The problem of identification of continuous, uncertain nonlinear systems in the presence of bounded disturbances is implemented using dynamic neural networks. The proposed neural identifier guarantees a bound for the state estimation error. This bound turns out to be a linear combination of internal and external uncertainty levels.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka